2022
DOI: 10.1093/plphys/kiac022
|View full text |Cite
|
Sign up to set email alerts
|

DNA-free CRISPR-Cas9 gene editing of wild tetraploid tomato Solanum peruvianum using protoplast regeneration

Abstract: Wild tomatoes (Solanum peruvianum) are important genomic resources for tomato research and breeding. Development of a foreign DNA-free CRISPR-Cas delivery system has potential to mitigate public concern about genetically modified organisms. Here, we established a DNA-free CRISPR-Cas9 genome editing system based on an optimized protoplast regeneration protocol of S. peruvianum, an important resource for tomato introgression breeding. We generated mutants for genes involved in small interfering RNAs (siRNA) biog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…A DNA-free genome editing method requires efficient and reproducible shoot regeneration from single cells, which is still a challenge and can be highly genotype dependent (Peres et al 2001 ). A recent study reported protoplast regeneration via a DNA-free method on wild tomato, which is the closest study so far to cultivated tomato (Lin et al 2022 ). Based on a previously published protocol for cultivated tomato protoplast genome editing via RNP-based CRISPR/Cas9 (Nicolia et al 2021a ), we have improved the protoplast isolation process and solved the challenge of shoot regeneration from RNP-transfected protoplasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A DNA-free genome editing method requires efficient and reproducible shoot regeneration from single cells, which is still a challenge and can be highly genotype dependent (Peres et al 2001 ). A recent study reported protoplast regeneration via a DNA-free method on wild tomato, which is the closest study so far to cultivated tomato (Lin et al 2022 ). Based on a previously published protocol for cultivated tomato protoplast genome editing via RNP-based CRISPR/Cas9 (Nicolia et al 2021a ), we have improved the protoplast isolation process and solved the challenge of shoot regeneration from RNP-transfected protoplasts.…”
Section: Discussionmentioning
confidence: 99%
“…Although a high editing efficiency has been reported on tomato calli from transfected protoplasts of cultivated tomato, the shoot regeneration from RNP-transfected protoplasts is a bottleneck (Nicolia et al 2021a ). Very recently, (Lin et al 2022 ) reported the successful protoplast regeneration of wild tomato ( Solanum peruvianum ) harboring CRISRP/Cas9 mutations, with a mutation rate varying from 8.3% to 63.6%. However, for cultivated tomato, there are only a few old reports published on plant regeneration from unedited protoplasts (Morgan and Cocking 1982 ; Sakata et al 1987 ; Tan et al 1987 ).…”
Section: Introductionmentioning
confidence: 99%
“…A DNA-free genome editing method requires e cient and reproducible shoot regeneration from single cells, which is still a challenge and can be highly genotype dependent (Peres et al 2001). A recent study reported protoplast regeneration via a DNA-free method on wild tomato, which is the closest study so far to cultivated tomato (Lin et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although a high editing e ciency has been reported on tomato calli from transfected protoplasts of cultivated tomato, the shoot regeneration from RNP-transfected protoplasts is a bottleneck (Nicolia et al 2021). Very recently (Lin et al 2022) reported the successful protoplast regeneration on wild tomato (Solanum peruvianum) harbouring CRISRP/Cas9 mutations, with a mutation rate varying from 8.3-63.6%. However, for cultivated tomato, there are only a few old reports published on plant regeneration from unedited protoplasts (Morgan and Cocking 1982 ;Sakata et al 1987;Tan et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Protoplasts are a useful tool for implementing and monitoring HR-based genome editing ( Beard et al, 2021 ; Wright et al, 2005 ; Townsend et al, 2009 ; Puchta and Fauser, 2013 ; Zhu et al, 2020 ; Hsu et al, 2021 ). Working with protoplasts enables the convenient and efficient delivery of large quantities of donor template as well as DNA that encodes for sequence-specific nucleases ( Sant’Ana et al, 2020 ; Nicolia et al, 2021 ; Lin et al, 2022 ). It has been hypothesized that efficient delivery of large amounts of donor template results in increased HR-mediated GT efficiency ( Baltes et al, 2014 ).…”
Section: Improving Hr Frequency By Increasing Donor Template Dosagementioning
confidence: 99%